ICU performance metrics and ICU outcomes - Madi, Meghana Deepak; A.K., Ajith Kumar (Journal of Nepalese Society of Critical Care Medicine, 2024)
Quality indicators (QIs) are integral to the operation of modern Intensive Care Units (ICUs). Over the years, impetus on quality patient care has greatly increased. The quality standards used in the industrial, educational sectors were tweaked to fit the needs of the health care sector. Effective quality indicators ensure treatment is safe, effective, efficient, timely, and patient-centred. Meanwhile, they should also help in identifying the deficiencies in the present health care system and rectify them. The QIs have garnered interest in the recent years as various national and international accreditation bodies have endorsed them to certify the hospitals. The World Patient Safety Day is being celebrated every year on September 17 since 2019. This clearly shows that integrating patient safety with health care is pivotal in ensuring universal health coverage. In this mini review, we will be providing a brief overview of the various quality indicators (QIs) that are routinely used, role of the accreditation bodies in ensuring quality care to the patients and the future of quality indicators.